Antimicrobial evaluation of copper sulfate (II) on strains of Enterococcus faecalis. In vitro study. - Marisol Sierra; Aldo Sanhueza; Rául Alcántara; Gabriela Sánchez (Universidad de Concepción., 2013)
Introduction: Controlling Enterococcus faecalis is of vital importance in endodontics, as this pathogen is associated with endodontic failure. Experimental evidence has shown that copper has antibacterial activity against other pathogens with similar characteristics. The objective of this study was to determine the antimicrobial activity of copper (II) or cupric (SC-II) sulfate on strains of Enterococcus faecalis and to compare it with the most commonly used antimicrobials. Methodology: We used 33 strains of Enterococcus faecalis isolated from different clinical pictures in different Chilean hospitals. The minimum inhibitory concentration (MIC) of SC-II, chlorhexidine and calcium hydroxide was determined by the broth microdilution technique, following the recommendations given by the Clinical and Laboratory Standards Institute. Results: The MIC for CHX varied in the range of 5-10µg/ml; SC-II from 1.5 to 12 µg/ml, and HC was >32mg/ml. The geometric mean of SC-II was 6µg/ml, lower than that of CHX, which was 7.29µg/ml. Conclusions: SC-II showed antimicrobial activity at lower concentrations than CHX. HC (which could have been affected by the buffer effect of the broth microdilution technique) showed high values, not comparable to other compounds. We suggest carrying out further studies on the properties of SC-II, such assessing its biocompatibility and reaction with other materials to be used clinically in endodontic therapy.